Influence of Meteorological Conditions on Effectiveness of Acoustic Screens – Measurements and Computations - RUDNO–RUDZIŃSKA, Barbara; MALEC, Tomasz; SAWA, Łukasz (Archives of Acoustics, 2008)
The paper presents the results of simulation and field studies of the effectiveness of road acoustic screens. In the simulation studies the influence of the declared weather conditions on the predicted acoustic screen effectiveness determined for different field conditions by different methods is analyzed. A comparative analysis of the results of screen effectiveness computations and measurements for three real systems of acoustic screens located by national roads in urbanized areas for different times of day is made.